Clinical Observations on the Treatment of Ramsay Hunt Syndrome by Blood-letting Puncture and Cupping as Main Therapy - 宋亚光 赵振春 袁慧 (Journal of acupuncture and tuina science, 2005)
Purpose: To investigate the clinical efficacy of blood-letting puncture and cupping in cooperation with acupuncture and moxibustion for treating Ramsay Hunt syndrome. A treatment group of 32 cases was treated by blood-letting puncture with plum-blossom needle and cupping in cooperation with acupuncture and moxibustion and a control group of 32 cases, with acupuncture and moxibustion, and andaciclovir. Results and conclusion: The cure and marked effectiveness rate was 81.2% in the treatment group and 56.2% in the control group after 4 courses of treatment. It was higher in the treatment group than in the control group (P <0.05). The short-term otalgia-relieving rate was also significantly higher in the treatment group than in the control group (P<0.01).